Bibliometric Analysis of Cooperative Learning (1974–2023) - Badrus Syamsi (Scientia Publica Media, 2024)
The importance of cooperative learning in achieving educational goals cannot be overlooked. According to existing literature, cooperative learning methods have proven to be effective in enhancing student achievement and fostering collaboration among them. A study conducted a comprehensive bibliometric analysis spanning the period 1974–2023 to explore the status and trends of cooperative learning implementation. In this bibliometric analysis, Samples were drawn from 4,367 refereed journal articles in the Scopus database. The research findings encompass several key points, including the peak publication in 2022 with 379 papers, the dominance of the keyword “cooperative learning,” the work of Dorigo, M and Gambardella, L.M as the most frequently cited documents, and David W. Johnson as the most prolific author. Journals such as the Journal of Chemical Education, Sustainability Switzerland, and Primus were also classified among the best, as well as institutions like the University of Minnesota Twin Cities, Arizona State University, and The University of Queensland. Furthermore, the United States and China are recognized as the most influential countries in the development of cooperative learning. The study’s conclusion provides a valuable contribution by presenting a comprehensive overview, mapping the scientific landscape, and offering directions for the future development of this teaching method.